STUDIES ON THE PHYSIOLOGY OF RICKETTSIAE IV. : Folic Acids of Coxiella Burnetii - Mattheis, Martha S. (1963)
Mattheis, Martha S. (University of Kansas, Lawrence), M. Silverman, and D. Paretsky. Studies on the physiology of rickettsiae. IV. Folic acids of Coxiella burnetii. J. Bacteriol. 85:37–41. 1963.—Yolk, yolk sac, and embryo tissues of uninfected eggs, and those infected with Coxiella burnetii, were analyzed for folic acid derivatives by employing diethylaminoethyl (DEAE)-cellulose column chromatography. Infected tissues contained quantitatively less folate, but the elution profiles of both infected and uninfected tissues were identical. Purified C. burnetii contained some types of folate apparently unique to these rickettsiae, and not found in infected tissue. The major folate fraction of C. burnetii was partially characterized by (i) elution position from DEAE columns; (ii) treatment with conjugase; (iii) growth response by Lactobacillus casei, Streptococcus faecalis R, and Pediococcus cerevisiae; and (iv) response to oxidation, reduction, and formylation.